Method for preparing hydrophobic coating on magnesium alloy surface through one-step electrodeposition
By performing one-step electrodeposition on the surface of the magnesium alloy, the problems of complex preparation steps, high cost and non-density coating in the prior art are solved, and the efficient corrosion resistance of the magnesium alloy is improved.
Patent Information
- Application Number
- CN202510116702.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-18
AI Technical Summary
The prior art method of preparing hydrophobic coatings on the surface of magnesium alloys has defects such as complex preparation steps, high cost, and non-density coatings, and cannot effectively meet the corrosion protection needs of magnesium alloys.
A one-step electrodeposition method is used to prepare a hydrophobic coating on the surface of the magnesium alloy. The specific steps include annealing, grinding and cleaning the magnesium alloy sample, and then electrodeposition in an ethanol solution of cerium nitrate and stearic acid to form a flat and dense hydrophobic coating.
The corrosion resistance of magnesium alloy samples is significantly improved, the preparation method is simple, and only one step of electrodeposition is required, industrialization costs are reduced, and a coating with good hydrophobicity is formed.
Smart Images

Figure CN119843331A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a hydrophobic coating by one-step electrodeposition on the surface of a magnesium alloy, belonging to the technical field of corrosion-resistant hydrophobic coatings. Background Art
[0002] As a kind of lightweight and high-strength structural material, magnesium alloy has the advantages of high specific strength, low density, high thermal conductivity, high damping, good machinability, good degradability and biocompatibility. These excellent properties make magnesium alloy not only used in specific occasions such as automobile, aerospace, communication, electronics, medical and other industries, but also attract much attention in the emerging new energy industry.
[0003] In practical applications, magnesium alloys face diverse and complex corrosion environments and are often used in corrosive environments such as high temperature and high humidity, industrial atmosphere, and marine atmosphere. In addition, magnesium alloys are hydrophilic metal materials with low standard electrode potential, poor corrosion resistance, and particularly active chemical properties, which lead to corrosion when used in aqueous or atmospheric media. The corrosion phenomenon not only reduces the quality of parts, but also restricts the service life of the overall product, thus hindering the use of magnesium alloys in real life. Therefore, although magnesium alloys have many advantages, their corrosion problem is one of the current research focuses and has become the main shortcoming restricting their widespread application.
[0004] Studies have shown that forming a hydrophobic coating on the surface of a metal substrate can effectively inhibit the direct contact between the corrosive medium and the metal substrate. Among the existing methods for preparing hydrophobic coatings, the electrodeposition method is very competitive due to its advantages such as easy control, simplicity, low cost, and environmental friendliness. Therefore, the preparation of hydrophobic coatings by electrodeposition on the surface of magnesium alloys has become a research hotspot for magnesium alloy corrosion protection in recent years.
[0005] Patent CN116288578A discloses a method for preparing a super-hydrophobic hydroxyapatite coating on a magnesium alloy surface, and the present invention relates to a method for preparing a super-hydrophobic hydroxyapatite coating on a magnesium alloy surface, first, pre-treating and ultrasonically cleaning the magnesium alloy; then configuring an electrodeposition solution, using graphite as an anode and a magnesium alloy substrate as a cathode, preparing a calcium-phosphorus coating on the magnesium alloy surface by an electrodeposition process, and then placing a sample of the surface-plated calcium-phosphorus coating in a certain concentration of NaOH solution, and heating in a water bath for 2-4h, keeping warm at 70-90°C, obtaining a hydroxyapatite coating; finally, the above-mentioned sample is immersed in anhydrous stearic acid ethanol solution and chemically modified to reduce its surface energy, so as to obtain a coating with super-hydrophobic properties. Although the hydroxyapatite super-hydrophobic coating prepared by the patent on the surface of a magnesium alloy can significantly reduce the initial corrosion of the magnesium alloy, there are problems such as the coating being not dense, having many defects, and having poor bonding strength with the substrate, and the patent preparation process is complicated, and chemical conversion treatment and surface low-energy modification are also required after electrodeposition post-treatment, and the industrialization cost is relatively high.
[0006] Patent CN116752213A discloses a post-treatment method for cathode deposition sealing of magnesium alloy micro-arc oxidation coating, the coating consists of two parts, including a magnesium alloy micro-arc oxidation coating on the substrate, and a corrosion-resistant hydrophobic coating deposited on the surface of the micro-arc oxidation layer, the substrate micro-arc oxidation coating is prepared in alkaline silicate; the post-treatment solution is composed of stearic acid, ethanol, and nitrate, the magnesium alloy sample after micro-arc oxidation treatment is the negative electrode, the carbon rod is the positive electrode, and a DC power supply is used for electrodeposition. After a certain period of electrodeposition, electrophoretic paint is added to the post-treatment solution, and then the electrodeposition is continued to obtain a corrosion-resistant hydrophobic micro-arc oxidation coating. Although this patent can prepare a hydrophobic coating on the surface of a magnesium alloy to improve the corrosion resistance of the magnesium alloy, the patent first electrodeposit the pre-treated sample during the electrodeposition process, and then continue to electrodeposit the pre-treated sample through electrophoretic paint, which requires two-step electrodeposition treatment, and the preparation steps are complicated and require specific equipment support, and the industrialization cost is high.
[0007] In summary, the current method of preparing hydrophobic coating by electrodeposition on the surface of magnesium alloy usually has defects such as complex preparation steps, high cost, and loose coating, and cannot meet the corrosion protection needs of magnesium alloy well. Summary of the invention
[0008] In view of the above problems existing in the prior art, the object of the present invention is to provide a method for preparing a hydrophobic coating on the surface of a magnesium alloy by one-step electrodeposition.
[0009] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:
[0010] A method for preparing a hydrophobic coating on a magnesium alloy surface by one-step electrodeposition comprises the following steps:
[0011] a) cutting the magnesium alloy substrate to obtain a cut magnesium alloy sample;
[0012] b) annealing, grinding and cleaning the cut magnesium alloy samples in sequence to obtain pretreated magnesium alloy samples;
[0013] c) first dissolving cerium nitrate (specifically cerium nitrate hexahydrate) and stearic acid in ethanol to prepare cerium nitrate ethanol solution and stearic acid ethanol solution respectively, and then mixing the cerium nitrate ethanol solution and the stearic acid ethanol solution evenly to obtain an electrolyte solution; using the pretreated magnesium alloy sample obtained in step b) as the cathode and graphite as the anode, immersing the positive and negative electrodes in the electrolyte solution, with a spacing of 15 to 25 mm between the positive and negative electrodes, and the temperature of the electrolyte solution being 20 to 30° C., and electrodepositing at 20 to 50 V for 1 to 3 hours. After the electrodeposition is completed, taking out the magnesium alloy sample, cleaning it, and drying it, preparing a hydrophobic coating on the surface of the magnesium alloy, and obtaining a magnesium alloy sample with a hydrophobic coating on the surface.
[0014] In one embodiment, in step a), the magnesium alloy substrate is a ZK60 magnesium alloy substrate, and the magnesium alloy substrate is cut into magnesium alloy samples of 5 mm×10 mm×10 mm by wire cutting process.
[0015] In one implementation scheme, in step b), during the annealing treatment, the annealing temperature is 573K-673K, and the annealing time is 1 to 4 hours.
[0016] In one embodiment, in step b), during the grinding treatment, 320#, 800#, and 1500# sandpapers are used in sequence to grind the surface of the magnesium alloy sample in mutually perpendicular directions until the surface is flat and smooth.
[0017] In one embodiment, in step b), the cleaning process is performed using anhydrous ethanol.
[0018] In one embodiment, in step c), in the electrolyte solution, the concentration of cerium nitrate is 0.03-0.05 mol / L, and the concentration of stearic acid is 0.03-0.05 mol / L.
[0019] Compared with the prior art, the present invention has the following significant beneficial effects:
[0020] The present invention first anneals, polishes and cleans the magnesium alloy sample and then performs an electrodeposition treatment, thereby forming a smooth and dense hydrophobic coating on the surface of the magnesium alloy sample, thereby significantly improving the corrosion resistance of the magnesium alloy sample. The preparation method is simple, and only one-step electrodeposition is required to form the hydrophobic coating on the surface of the magnesium alloy sample. Compared with the prior art, the present invention not only produces unexpected technical effects, but also has significant advancement. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a SEM image of a magnesium alloy sample having a hydrophobic coating on its surface prepared in Example 1;
[0022] Figure 2 XRD diagram of the magnesium alloy sample with a hydrophobic coating on the surface prepared in Example 1;
[0023] Figure 3 This is the FTIR graph of the magnesium alloy sample with a hydrophobic coating on the surface prepared in Example 1. DETAILED DESCRIPTION
[0024] The technical scheme of the present invention is further described in detail and completely below in conjunction with the examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or according to the conditions recommended by the manufacturer.
[0025] Example 1
[0026] a) The ZK60 magnesium alloy substrate is cut into magnesium alloy samples of 5 mm × 10 mm × 10 mm by wire cutting process;
[0027] b) the cut magnesium alloy samples are first subjected to annealing treatment (specifically: the cut magnesium alloy samples are placed in a box-type resistance furnace and annealed at a temperature of 623K for 2 hours), and then the annealed magnesium alloy samples are first polished in mutually perpendicular directions using 320#, 800#, and 1500# sandpapers in sequence until the surfaces are flat and smooth, and then cleaned with anhydrous ethanol, and after cleaning, placed on weighing paper to dry naturally, to obtain pretreated magnesium alloy samples;
[0028] c) first dissolving cerium nitrate hexahydrate and stearic acid in ethanol respectively to prepare cerium nitrate ethanol solution and stearic acid ethanol solution, and then mixing the cerium nitrate ethanol solution and the stearic acid ethanol solution uniformly to obtain an electrolyte solution (first preparing cerium nitrate ethanol solution and stearic acid ethanol solution respectively, and then mixing the cerium nitrate ethanol solution and the stearic acid ethanol solution uniformly to obtain an electrolyte solution, compared with directly dissolving cerium nitrate hexahydrate and stearic acid in ethanol at the same time to prepare an electrolyte solution, the dissolution process of cerium nitrate and stearic acid can be better controlled, avoiding local excessive concentration or uneven reaction, and avoiding side reactions), in the electrolyte solution, the concentrations of cerium nitrate and stearic acid are both 0.03 mol / L; using the pretreated magnesium alloy sample obtained in step b) as the cathode and graphite as the anode, immersing the positive and negative electrodes in the electrolyte solution, the interval between the positive and negative electrodes is 20 mm, the temperature of the electrolyte solution is 25° C., and electrodeposition is performed at 40 V for 1 hour. After the electrodeposition is completed, the magnesium alloy sample is taken out, cleaned, and dried to prepare a hydrophobic coating on the surface of the magnesium alloy to obtain a magnesium alloy sample with a hydrophobic coating on the surface.
[0029] Figure 1 This is a SEM image of the magnesium alloy sample with a hydrophobic coating on the surface prepared in this embodiment; it can be seen from the image that the surface of the magnesium alloy presents a smooth and dense coating morphology.
[0030] Figure 2 is an XRD pattern of the magnesium alloy sample with a hydrophobic coating on the surface prepared in this embodiment; Figure 3 FTIR graph of the magnesium alloy sample with a hydrophobic coating on the surface prepared in this embodiment; Figure 2 and Figure 3 It can be seen that the surface coating of the magnesium alloy formed substances such as Mg(OH)2 and Ce(OH)4, and stearate existed on the surface, indicating that the electrolyte solution containing cerium nitrate and stearic acid was successfully electrodeposited on the surface of the magnesium alloy.
[0031] The contact angle of the magnesium alloy sample with a hydrophobic coating on the surface prepared in this embodiment was tested using an optical contact angle meter. The test results showed that the contact angle of the magnesium alloy sample was 107.798°, indicating that the coating on the surface of the magnesium alloy sample prepared in this embodiment has good hydrophobicity.
[0032] The magnesium alloy sample with a hydrophobic coating on the surface prepared in this embodiment was tested for corrosion resistance. The specific test method is: using an electrochemical workstation, the test was carried out under a three-electrode system (using a 218-type silver / silver chloride single salt bridge electrode as a reference electrode, a 213-type platinum electrode as a counter electrode, and an experimental sample with an exposed area of 0.2 cm² as a working electrode), and the corrosive medium was a 3.5wt.% NaCl solution. The test results show that:
[0033] The self-corrosion potential of the magnesium alloy sample with a hydrophobic coating on the surface prepared in this embodiment is -1.435 V, and the self-corrosion current density is 1.449×10 -7 A.cm -2 , the impedance value is 30106ohm·cm²;
[0034] Under the same conditions, the self-corrosion potential of the original magnesium alloy sample is -1.39V, and the self-corrosion current density is 7.66×10 -5 A.cm -2 , the impedance value is 277.2ohm·cm²;
[0035] It can be seen that the corrosion current of the magnesium alloy sample with a hydrophobic coating on the surface of the present embodiment is 2 orders of magnitude lower than the corrosion current density of the original magnesium alloy sample, and the impedance value is increased by 2 orders of magnitude, indicating that the hydrophobic coating significantly improves the corrosion resistance of the magnesium alloy sample.
[0036] Example 2
[0037] The only difference between this embodiment and embodiment 1 is that during electrodeposition, the concentrations of cerium nitrate and stearic acid in the electrolyte solution used are both 0.04 mol / L, and the rest of the contents are the same as those described in embodiment 1.
[0038] The contact angle of the magnesium alloy sample with a hydrophobic coating on the surface prepared in this embodiment is 112.751°, indicating that the coating on the surface of the magnesium alloy sample has good hydrophobicity.
[0039] The self-corrosion potential of the magnesium alloy sample with a hydrophobic coating on the surface prepared in this embodiment is -1.362 V, and the self-corrosion current density is 1.771×10 -7 A.cm -2 , its impedance value is 77311ohm·cm²;
[0040] Under the same conditions, the self-corrosion potential of the original magnesium alloy sample is -1.39 V, and the self-corrosion current density is 7.66×10 -5 A.cm -2 , the impedance value is 277.2ohm·cm²;
[0041] It can be seen that the corrosion current of the magnesium alloy sample with a hydrophobic coating on the surface of the present embodiment is 2 orders of magnitude lower than the corrosion current density of the original magnesium alloy sample, and the impedance value is increased by 2 orders of magnitude, indicating that the hydrophobic coating significantly improves the corrosion resistance of the magnesium alloy sample.
[0042] Example 3
[0043] The only difference between this embodiment and embodiment 1 is that during electrodeposition, the concentrations of cerium nitrate and stearic acid in the electrolyte solution used are both 0.05 mol / L, and the rest of the contents are the same as those described in embodiment 1.
[0044] The contact angle of the magnesium alloy sample with a hydrophobic coating on the surface prepared in this embodiment is 119.886°, indicating that the coating on the surface of the magnesium alloy sample has good hydrophobicity.
[0045] The self-corrosion potential of the magnesium alloy sample with a hydrophobic coating on the surface prepared in this embodiment is -1.364 V, and the self-corrosion current density is 9.579×10 -8 A.cm -2 , its impedance value is 84044ohm·cm²;
[0046] Under the same conditions, the self-corrosion potential of the original magnesium alloy sample is -1.39 V, and the self-corrosion current density is 7.66×10 -5 A.cm -2 , the impedance value is 277.2ohm·cm²;
[0047] It can be seen that the corrosion current of the magnesium alloy sample with a hydrophobic coating on the surface of the present embodiment is reduced by 3 orders of magnitude compared with the corrosion current density of the original magnesium alloy sample, and the impedance value is increased by 2 orders of magnitude, indicating that the hydrophobic coating significantly improves the corrosion resistance of the magnesium alloy sample.
[0048] Example 4
[0049] The difference between this embodiment and embodiment 1 is that during the electrodeposition, the electrodeposition is carried out at 40 V for 2 hours, and the rest of the contents are the same as those described in embodiment 1.
[0050] The contact angle of the magnesium alloy sample with a hydrophobic coating on the surface prepared in this embodiment is 126.765°, indicating that the coating on the surface of the magnesium alloy sample has good hydrophobicity.
[0051] The self-corrosion potential of the magnesium alloy sample with a hydrophobic coating on the surface prepared in this embodiment is -1.377 V, and the self-corrosion current density is 4.163×10 -8 A.cm -2 , its impedance value is 156353ohm·cm²;
[0052] Under the same conditions, the self-corrosion potential of the original magnesium alloy sample is -1.39 V, and the self-corrosion current density is 7.66×10 -5 A.cm -2 , the impedance value is 277.2ohm·cm²;
[0053] It can be seen that the corrosion current of the magnesium alloy sample with a hydrophobic coating on the surface of the present embodiment is reduced by 3 orders of magnitude compared with the corrosion current density of the original magnesium alloy sample, and the impedance value is increased by 3 orders of magnitude, indicating that the hydrophobic coating significantly improves the corrosion resistance of the magnesium alloy sample.
[0054] Example 5
[0055] The difference between this embodiment and embodiment 1 is that during the electrodeposition, the electrodeposition is carried out at 40 V for 3 hours, and the rest of the contents are the same as those described in embodiment 1.
[0056] The contact angle of the magnesium alloy sample with a hydrophobic coating on the surface prepared in this embodiment is 135.006°, indicating that the coating on the surface of the magnesium alloy sample has good hydrophobicity.
[0057] The self-corrosion potential of the magnesium alloy sample with a hydrophobic coating on the surface prepared in this embodiment is -1.345 V, and the self-corrosion current density is 1.284×10 -7 A.cm -2 , its impedance value is 187050 ohm·cm²;
[0058] Under the same conditions, the self-corrosion potential of the original magnesium alloy sample is -1.39 V, and the self-corrosion current density is 7.66×10 -5 A.cm -2 , the impedance value is 277.2ohm·cm²;
[0059] It can be seen that the corrosion current of the magnesium alloy sample with a hydrophobic coating on the surface of the present embodiment is reduced by 2 orders of magnitude compared with the corrosion current density of the original magnesium alloy sample, and the impedance value is increased by 3 orders of magnitude, indicating that the hydrophobic coating significantly improves the corrosion resistance of the magnesium alloy sample.
[0060] Example 6
[0061] The difference between this embodiment and embodiment 1 is that during the electrodeposition, the concentrations of cerium nitrate and stearic acid in the electrolyte solution used are both 0.05 mol / L, and the electrodeposition is carried out at 40 V for 2 hours. The rest of the contents are the same as those described in embodiment 1.
[0062] The contact angle of the magnesium alloy sample with the hydrophobic coating on the surface prepared in this embodiment is 128.9°, indicating that the coating on the surface of the magnesium alloy sample has good hydrophobicity.
[0063] The self-corrosion potential of the magnesium alloy sample with a hydrophobic coating on the surface prepared in this embodiment is -1.493 V, and the self-corrosion current density is 8.407×10 -8 A.cm -2 , its impedance value is 139290 ohm·cm²;
[0064] Under the same conditions, the self-corrosion potential of the original magnesium alloy sample is -1.39 V, and the self-corrosion current density is 7.66×10 -5 A.cm -2 , the impedance value is 277.2ohm·cm²;
[0065] It can be seen that the corrosion current of the magnesium alloy sample with a hydrophobic coating on the surface of the present embodiment is reduced by 3 orders of magnitude compared with the corrosion current density of the original magnesium alloy sample, and the impedance value is increased by 3 orders of magnitude, indicating that the hydrophobic coating significantly improves the corrosion resistance of the magnesium alloy sample.
[0066] In combination with Examples 1 to 6, it can be seen that the present invention first anneals, polishes, and cleans the magnesium alloy sample and then uses an ethanol solution of cerium nitrate and stearic acid as an electrolyte solution for electrodeposition. Only one-step electrodeposition is required to form a flat, dense, and hydrophobic coating with good hydrophobicity on the surface of the magnesium alloy, which can significantly improve the corrosion resistance of the magnesium alloy sample. In addition, the specific electrodeposition conditions used during electrodeposition (including the concentrations of cerium nitrate and stearic acid in the electrolyte solution, the electrodeposition time, the electrodeposition voltage, etc.) also have a certain influence on the hydrophobicity and corrosion resistance of the prepared magnesium alloy sample.
[0067] Comparative Example 1
[0068] The difference between this embodiment and embodiment 1 is that the magnesium alloy sample is not annealed before electrodeposition, and the rest of the contents are the same as those described in embodiment 1. The specific preparation process is as follows:
[0069] a) The ZK60 magnesium alloy substrate is cut into magnesium alloy samples of 5 mm × 10 mm × 10 mm by wire cutting process;
[0070] b) The cut magnesium alloy samples were first polished in mutually perpendicular directions using 320#, 800#, and 1500# sandpapers in sequence until their surfaces were flat and smooth, and then cleaned with anhydrous ethanol. After cleaning, they were placed on weighing paper and naturally air-dried to obtain pretreated comparative magnesium alloy samples;
[0071] c) dissolving cerium nitrate hexahydrate and stearic acid in ethanol respectively to prepare cerium nitrate ethanol solution and stearic acid ethanol solution, and then mixing the cerium nitrate ethanol solution and the stearic acid ethanol solution evenly to obtain an electrolyte solution, wherein the concentrations of cerium nitrate and stearic acid in the electrolyte solution are both 0.03 mol / L; using the pretreated comparative magnesium alloy sample obtained in step b) as the cathode and graphite as the anode, immersing the positive and negative electrodes in the electrolyte solution, with a spacing of 20 mm between the positive and negative electrodes, and the temperature of the electrolyte solution being 25° C., and electrodepositing at 40 V for 1 hour. After the electrodeposition is completed, taking out the magnesium alloy sample, cleaning, and drying, and preparing a comparative coating on the surface of the magnesium alloy to obtain a magnesium alloy sample with a comparative coating on the surface.
[0072] The contact angle of the magnesium alloy sample with a comparative coating on the surface prepared in this comparative example is 98.27°, while under the same conditions, the contact angle of the magnesium alloy sample prepared in Example 1 is 107.798°, indicating that although the coating on the surface of the magnesium alloy sample prepared in this comparative example has a certain hydrophobicity, the hydrophobicity is far inferior to the coating on the surface of the magnesium alloy sample prepared in Example 1, indicating that although the preparation method of Comparative Example 1 can form a hydrophobic coating on the surface of the magnesium alloy, the hydrophobicity of the formed coating is far inferior to the hydrophobic coating formed by the preparation method in Example 1.
[0073] The self-corrosion potential of the magnesium alloy sample with the comparative coating on the surface prepared in this comparative example is -1.381V, and the self-corrosion current density is 2.351×10 -6 A.cm -2 , its impedance value is 3881ohm·cm²;
[0074] Under the same conditions, the self-corrosion potential of the original magnesium alloy sample is -1.39 V, and the self-corrosion current density is 7.66×10 -5 A.cm -2 , the impedance value is 277.2ohm·cm²;
[0075] The self-corrosion potential of the magnesium alloy sample with a hydrophobic coating on the surface prepared in Example 1 is -1.435 V, and the self-corrosion current density is 1.449×10 -7 A.cm -2 , the impedance value is 30106ohm·cm²;
[0076] It can be seen that, although the corrosion current density of the magnesium alloy sample with the comparative coating on the surface of the comparative example is lower than that of the original magnesium alloy sample, the reduction is not as great as that of the magnesium alloy sample in Example 1; the impedance value of the magnesium alloy sample of the comparative example is higher than that of the original magnesium alloy sample, but the increase is not as great as that of the magnesium alloy sample in Example 1, which indicates that although the preparation method of comparative example 1 can improve the corrosion resistance of the magnesium alloy sample, the improvement effect is not as significant as that of the preparation method in Example 1.
[0077] Comparative Example 2
[0078] The difference between this comparative example and Example 1 is that the magnesium alloy sample is not subjected to electrodeposition treatment, and the specific preparation process is as follows: a) the ZK60 magnesium alloy substrate is cut into magnesium alloy samples of 5 mm×10 mm×10 mm by wire cutting process;
[0079] b) The cut magnesium alloy samples are first annealed (specifically: the cut magnesium alloy samples are placed in a box-type resistance furnace and annealed for 2 hours at a temperature of 623K), and then the annealed magnesium alloy samples are first polished in mutually perpendicular directions using 320#, 800#, and 1500# sandpapers in sequence until the surface is flat and smooth, and then cleaned with anhydrous ethanol. After cleaning, they are placed on weighing paper to air dry naturally to obtain magnesium alloy samples.
[0080] The self-corrosion potential of the magnesium alloy sample prepared in this comparative example is -1.578 V, and the self-corrosion current density is 4.004×10 -5 A.cm -2 , its impedance value is 676.67ohm·cm²;
[0081] Under the same conditions, the self-corrosion potential of the original magnesium alloy sample is -1.39 V, and the self-corrosion current density is 7.66×10 -5 A.cm -2 , the impedance value is 277.2ohm·cm²;
[0082] The self-corrosion potential of the magnesium alloy sample with a hydrophobic coating on the surface prepared in Example 1 is -1.435 V, and the self-corrosion current density is 1.449×10 -7 A.cm -2 , the impedance value is 30106ohm·cm²;
[0083] It can be seen that, although the corrosion current of the magnesium alloy sample in this comparative example is lower than the corrosion current density of the original magnesium alloy sample, the reduction is very small, and is far less than the reduction of the magnesium alloy sample in Example 1; the impedance value of the magnesium alloy sample in this comparative example is higher than that of the original magnesium alloy sample, but the increase is very small, and is far less than the increase of the magnesium alloy sample in Example 1. This shows that although the preparation method of comparative example 1 can improve the corrosion resistance of the magnesium alloy sample, the improvement effect is very slight, and is far less significant than the preparation method in Example 1.
[0084] Combining Example 1, Comparative Example 1 and Comparative Example 2, it can be seen that the corrosion resistance of the magnesium alloy sample prepared by annealing and electrodeposition in Example 1 is better than the corrosion resistance of the magnesium alloy sample prepared by only electrodeposition in Comparative Example 1 and only annealing in Comparative Example 2, indicating that there is a synergistic effect between annealing and electrodeposition.
[0085] Comparative Example 3
[0086] The difference between this comparative example and Example 1 is that the process conditions used in the annealing treatment and the electrodeposition treatment are different. The specific preparation process is as follows:
[0087] a) The ZK60 magnesium alloy substrate is cut into magnesium alloy samples of 5 mm × 10 mm × 10 mm by wire cutting process;
[0088] b) the cut magnesium alloy samples are first subjected to annealing treatment (specifically: the cut magnesium alloy samples are placed in a box-type resistance furnace and annealed at a temperature of 623K for 0.5 hours), and then the annealed magnesium alloy samples are first polished in mutually perpendicular directions using 320#, 800#, and 1500# sandpapers in sequence until the surfaces are flat and smooth, and then cleaned with anhydrous ethanol, and after cleaning, placed on weighing paper to dry naturally, to obtain pretreated magnesium alloy samples;
[0089] c) dissolving cerium nitrate hexahydrate and stearic acid in 50 ml of ethanol respectively to prepare an electrolyte solution, wherein the concentrations of cerium nitrate and stearic acid in the electrolyte solution are both 0.03 mol / L; taking the pretreated magnesium alloy sample obtained in step b) as the cathode and graphite as the anode, immersing the positive and negative electrodes in the electrolyte solution, with a spacing of 20 mm between the positive and negative electrodes, and the temperature of the electrolyte solution being 25° C., and electrodepositing at 10 V for 0.5 hour. After the electrodeposition is completed, taking out the magnesium alloy sample, cleaning it, and drying it, preparing a hydrophobic coating on the surface of the magnesium alloy, and obtaining a magnesium alloy sample having a hydrophobic coating on the surface.
[0090] The contact angle of the magnesium alloy sample with a comparative hydrophobic coating on the surface prepared in this comparative example is 97.16°. Although the contact angle is greater than 90°, it is much lower than the contact angle of the magnesium alloy samples prepared in Examples 1-6, indicating that the hydrophobicity of the magnesium alloy sample prepared in this comparative example is much lower than that of the magnesium alloy samples prepared in Examples 1-6.
[0091] The self-corrosion potential of the magnesium alloy sample with a comparative hydrophobic coating on the surface prepared in this comparative example is -1.358 V, and the self-corrosion current density is 1.908×10 -5 A.cm -2 , its impedance value is 1271ohm·cm 2 ;
[0092] Under the same conditions, the self-corrosion potential of the original magnesium alloy sample is -1.39 V, and the self-corrosion current density is 7.66×10 -5 A.cm -2 , the impedance value is 277.2ohm·cm²;
[0093] Combining Comparative Example 3 and Examples 1-6, it can be seen that although the corrosion current of the magnesium alloy sample in this comparative example is lower than that of the original magnesium alloy sample, the reduction is very small, which is far less than the reduction of the magnesium alloy samples in Examples 1-6. The impedance value of the magnesium alloy sample in this comparative example is higher than that of the original magnesium alloy sample, but the increase is very small, which is far less than the increase of the magnesium alloy samples in Examples 1-6. This shows that in the process of preparing the hydrophobic coating on the surface of the magnesium alloy in the present invention, the specific conditions used for annealing and electrodeposition have a certain influence on the hydrophobicity and corrosion resistance of the final product, and the specific conditions used for annealing and electrodeposition are unpredictable.
[0094] Finally, it should be pointed out that the above are only some preferred embodiments of the present invention and should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above contents of the present invention all fall within the scope of protection of the present invention.
Claims
1. A method for preparing a hydrophobic coating on a magnesium alloy surface by one-step electrodeposition, characterized in that: The steps include: a) cutting the magnesium alloy substrate to obtain a cut magnesium alloy sample; b) annealing, grinding and cleaning the cut magnesium alloy samples in sequence to obtain pretreated magnesium alloy samples; c) dissolving cerium nitrate and stearic acid in ethanol to prepare cerium nitrate ethanol solution and stearic acid ethanol solution respectively, and then mixing the cerium nitrate ethanol solution and the stearic acid ethanol solution evenly to obtain an electrolyte solution; taking the pretreated magnesium alloy sample obtained in step b) as the cathode and graphite as the anode, immersing the positive and negative electrodes in the electrolyte solution, with a spacing of 15 to 25 mm between the positive and negative electrodes, and the temperature of the electrolyte solution being 20 to 30° C., and electrodepositing at 20 to 50 V for 1 to 3 hours. After the electrodeposition is completed, taking out the magnesium alloy sample, cleaning it, and drying it, and preparing a hydrophobic coating on the surface of the magnesium alloy to obtain a magnesium alloy sample with a hydrophobic coating on the surface.
2. The method for preparing a hydrophobic coating by one-step electrodeposition on a magnesium alloy surface according to claim 1, characterized in that: In step a), the magnesium alloy substrate is a ZK60 magnesium alloy substrate, and the magnesium alloy substrate is cut into magnesium alloy samples of 5 mm×10 mm×10 mm by wire cutting process.
3. The method for preparing a hydrophobic coating on a magnesium alloy surface by one-step electrodeposition according to claim 1, characterized in that: In step b), during the annealing treatment, the annealing temperature is 573K-673K, and the annealing time is 1 to 4 hours.
4. The method for preparing a hydrophobic coating on a magnesium alloy surface by one-step electrodeposition according to claim 1, characterized in that: In step b), during the grinding process, 320#, 800#, and 1500# sandpapers are used in sequence to grind the surface of the magnesium alloy sample in directions perpendicular to each other until the surface is flat and smooth.
5. The method for preparing a hydrophobic coating on a magnesium alloy surface by one-step electrodeposition according to claim 1, characterized in that: In step b), anhydrous ethanol is used for cleaning.
6. The method for preparing a hydrophobic coating on a magnesium alloy surface by one-step electrodeposition according to claim 1, characterized in that: In step c), in the electrolyte solution, the concentration of cerium nitrate is 0.03-0.05 mol / L, and the concentration of stearic acid is 0.03-0.05 mol / L.